2017
DOI: 10.1109/tcsvt.2016.2589619
|View full text |Cite
|
Sign up to set email alerts
|

An Equalized Global Graph Model-Based Approach for Multicamera Object Tracking

Abstract: Non-overlapping multi-camera visual object tracking typically consists of two steps: single camera object tracking and inter-camera object tracking. Most of tracking methods focus on single camera object tracking, which happens in the same scene, while for real surveillance scenes, inter-camera object tracking is needed and single camera tracking methods can not work effectively. In this paper, we try to improve the overall multi-camera object tracking performance by a global graph model with an improved simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 62 publications
0
53
0
Order By: Relevance
“…An attributed graph, as its name implies, defines a set of values (attributes) for each vertex in a graph to represent the features extracted from the input video/image frame. The graph representation is utilized in combination with a particle filter [4], feature extraction using DCT coefficients [5], utilizing geometric transformation [6], learning-based structured graph matching [7], global-modeling graph with similarity metric for non-overlapping multi-camera object tracking [8], or utilizing non-RGB information in graph-based object tracking [9].…”
Section: Related Workmentioning
confidence: 99%
“…An attributed graph, as its name implies, defines a set of values (attributes) for each vertex in a graph to represent the features extracted from the input video/image frame. The graph representation is utilized in combination with a particle filter [4], feature extraction using DCT coefficients [5], utilizing geometric transformation [6], learning-based structured graph matching [7], global-modeling graph with similarity metric for non-overlapping multi-camera object tracking [8], or utilizing non-RGB information in graph-based object tracking [9].…”
Section: Related Workmentioning
confidence: 99%
“…In addition, to better achieve tracklet matching across multiple camera views, the minimum uncertainty gap-based measurement, i.e., using the lowest and highest similarity to define the lower and upper bounds of the similarity for two tracklets to obtain a distance metric, is applied to computing the matching result of two tracklets' PMCSHRs. Built upon the research of PMCSHR [62], Chen et al [63] equalize similarity metrics in the global graph based on appearance and motion features, and hence further reduce the number of mismatch errors in non-overlapping inter-camera human tracking so as to further improve human tracking performance across non-overlapping cameras. Table 6 lists several quantitative comparison results of GM-based tracking across non-overlapping cameras on NLPR datasets, using multiple camera tracking accuracy (MCTA) to evaluate the performance of GM-based tracking, where the higher the MCTA is, the better the performance of GM-based tracking.…”
Section: Gm-based Trackingmentioning
confidence: 99%
“…Milan et al constructed a carefully annotated dataset for Multi-Object Tracking Challenge 2016 [ 10 ]. In addition, the datasets which provided non-overlapping multi-camera videos covering the same objects were adopted in this paper provided by Chen et al [ 11 ] and Ristani et al [ 12 ]. No matter which dataset is adopted, there are still some common challenges: frequent occlusion among crowds, accurate determination of the beginning and end of a trajectory, similar appearance among pedestrians, and missing details due to low resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in order to handle the problem that the network can hardly converge effectively on large and complex datasets, a sigmoid normalize operation is applied. For multi-object tracking across cameras, we design two strategies: a simple sequence-to-sequence matching algorithm and tracking algorithm by embedding the feature extraction in EGTracker in [ 11 ]. The experiments have demonstrated that the proposed method can extract efficient features and improve the performance of tracking systems when applying the learned features.…”
Section: Introductionmentioning
confidence: 99%